The Method for Fabricating Proppant and Cenosphere Sand-Based Casting Molds Involving the Use of Binder Jetting 3D Printing with Furan Binder and Impregnation with Colloidal Silica Binder - Viacheslav E. Bazhenov; Ksenia A. Deputatova; Andrey A. Rizhsky; Yuri V. Tselovalnik; Andrey I. Bazlov; Stanislav V. Chernyshikhin; Andrey V. Koltygin; Alexey S. Anishchenko; Vladimir D. Belov; Evgenii Yu. Shchedrin (Journal of Manufacturing and Materials Processing)
Binder jetting is the most widely implemented additive technology for the fabrication of sand molds. However, the use of furan binder-jetting technology in the production of molds for vacuum casting is hindered by the thermal destruction of the furan binder accompanied by violent gas emission that occurs during the mold heating process. This investigation explores the potential of using the molds obtained via furan binder jetting 3D printing and further impregnation in colloidal silica binder and sintering. Two distinct sands, proppant and cenosphere, were utilized in the fabrication of the mold components exhibiting different thermal properties. An examination of the structure of the initial sands and samples produced via different impregnation and sintering regimes was conducted via scanning electron microscopy with energy dispersive X-ray spectroscopy, X-ray diffractometry, thermogravimetric analysis, and micro computed tomography. Furthermore, the bending mechanical properties and linear shrinkage of the samples were determined. The experimental findings demonstrated that the specific impregnation and sintering regimes examined in this study yielded sufficient mechanical properties for the casting molds and the structure with cristobalite bridges. The mold assembly, composed of proppant and cenosphere sands-based parts, was produced, and impeller nickel-based superalloy castings were fabricated. The findings of this study demonstrate that the utilization of a furan binder-jetting technique, in conjunction with impregnation in colloidal silica binder, is a promising technology for the manufacture of high-melting-temperature alloy casting.